OVERVIEW OF RELIGIUS IN GENERATION Z WITH GENERALIZED ANXIETY DISORDER (PSYCHOLOGY & MENTAL HEALTH) - Safirna, Naja Alyya; Fahmawati, Zaki Nur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Generalized Anxiety Disorder (GAD) is a mental health problem experienced by many Generation Z and can have a negative impact on daily life. This research aims to explore the role of religiosity as a coping mechanism in dealing with anxiety in individuals with GAD. Method: The method used is qualitative research with a descriptive phenomenological approach. Data was collected through in-depth interviews with two participants who were diagnosed with GAD by professionals. Data analysis was carried out using Giorgi's phenomenological method to identify patterns and meanings of participants' experiences. Results: The research results show that religiosity, which includes belief, religious practices such as prayer, dhikr, reading the Koran, and involvement in Islamic studies, provides psychological calm and helps individuals overcome anxiety. These findings confirm that religiosity plays a role in increasing psychological resilience and mental well-being. Novelty: This study provides new insight into the importance of a religious approach in supporting mental health in Generation Z who experience GAD.